EFFECTS OF THE PERCUTANEUOS ELECTROLYSIS THERAPY: A SYSTEMATIC REVIEW (Cuestiones de Fisioterapia, 2020)
Introduction: conventional treatments of certain chronic pathologies sometimes do not bring the expected results, so there is a need to seek new treatment techniques, such as Intratissue Percutaneous Electrolysis (IPE).he objective of this literature review is to establish the evidence in the literature on the physiological effects of the application of IPE in the organism. Material and methods: a systematic search of scientific literature according to the PRISMA regulations was carried out in Medline, Pub med, Scopus and Sport discus, during the months of January and February 2018 using the terms "electrolysis" and "percutaneous" joined together by the Boolean operator AND. Exclusion criteria were applied to all returned results and 13 works were finally obtained for review. The Jadad scale was used to determine the quality of the studies. Results: thirteen studies were included, which analyzed the effects of IPE in both humans and animals and in comparison, with other techniques or interventions. Many of these studies provided statistically significant data showing that after IPE pain is reduced and functionality im-proved, among other variables. Conclusions: the effects of IPE on the organism are beneficial, so in those pathologies in which conventional techniques do not obtain f positive results, it may represent a treatment option to be taken into account.